2008
DOI: 10.1182/blood-2008-01-132951
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood regulatory T-cell expansion and functional effects of tumor necrosis factor receptor family members OX40 and 4-1BB expressed on artificial antigen-presenting cells

Abstract: IntroductionAcute graft-versus-host disease (GVHD) is a significant cause of morbidity and mortality after allogeneic bone marrow transplantation (BMT) and occurs as a result of the activation, proliferation, and effector cell function of donor T cells that, along with the release of proinflammatory cytokines, result in tissue damage. 1 Recently, a subset of CD4 ϩ T cells with potent suppressor activity, CD4 ϩ 25 ϩ regulatory T cells (Tregs), 2 have been shown to inhibit alloreactive T-cell activation and effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
129
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 55 publications
13
129
1
Order By: Relevance
“…One study reported that mouse third-party Treg cells, when used in combination with rapamycin, prevented rejection of allogeneic bone marrow while rapamycin alone failed to do so (63), suggesting that the third-party Treg cells can survive and function in MHC-incompatible recipient hosts. In a more recent study, human third-party Treg cells were shown to be able to protect hosts from lethality in xenogeneic GVHD models (49). Purified third-party Treg cells, in the absence of contaminating APCs, may be very poorly immunogenic with respect to inducing cytolytic or humoral immune responses that might lead to their destruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that mouse third-party Treg cells, when used in combination with rapamycin, prevented rejection of allogeneic bone marrow while rapamycin alone failed to do so (63), suggesting that the third-party Treg cells can survive and function in MHC-incompatible recipient hosts. In a more recent study, human third-party Treg cells were shown to be able to protect hosts from lethality in xenogeneic GVHD models (49). Purified third-party Treg cells, in the absence of contaminating APCs, may be very poorly immunogenic with respect to inducing cytolytic or humoral immune responses that might lead to their destruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of previous barriers in expanding human Ag-specific Treg cells, there has been interest that anti-CD3/CD28-expanded polyclonal Treg cells might be the only approach to generate large numbers of Treg cells for therapeutic applications (43,45,46). Over the last few years, great effort has been made to improve anti-CD3/CD28-based expansion of human polyclonal Treg cells with the goal of improving the yield and purity of the expanded cells (45,(47)(48)(49)(50)(51). Our findings provide an approach to selectively expand alloantigen-specific Treg cells that can serve as a springboard to future development of alloantigen-specific Treg cell-based therapy in humans.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05; **P < 0.01; ***P < 0.001. (32)(33)(34)(35). We attempted to induce Treg proliferation in vitro using many different combinations of anti-CD3 and anti-CD28 antibodies, recombinant IL-2, TGF-β, and retinoic acid with or without TNFR25 agonistic antibody; in all cases, TNFR25 stimulation failed to enhance Treg proliferation in vitro, which indicated that additional signals were required (data not shown and Supplemental Table 1; supplemental material available online with this article; doi:10.1172/JCI42933DS1).…”
Section: Figurementioning
confidence: 99%
“…14 The effect of Tregs on NK cells (NK cell isolation kit, MACS; Miltenyi Biotec) or PBMNCs was tested after labeling with 5-carboxyfluorescein diacetate succinimide ester (CFSE) to assess proliferation induced by anti-CD3 mAb-coated beads (Dynal) or cytokines as indicated. We used the same suppression assay to evaluate patient PBMNCs collected at day 14 with healthy donor NK cells.…”
Section: -Carboxyfluorescein Diacetate Succinimide Ester Assay To Asmentioning
confidence: 99%